Improvement of thermal quality in rural houses using fiber cement blocks, in Masocruz, Puno region - Ccopa Peralta, William Josue (2023)
This research evaluates and proposes a thermal rural house built with cement blocks added Stipa Ichu fibers (fibre-cement), in order to save energy and improve the thermal comfort of the inhabitants, a technical evaluation of the materials used in the building was carried out. the construction of the house, the 7.5 m2 prototype house was built with the blocks, where the temperature inside a typical rural house in the area was evaluated and compared with the prototype house to the thermal variation reported a maximum of 22.2°C and a minimum of 10.1°C in the prototype house, while in the typical rural house a maximum of 14.6°C and a minimum of -2.3°C in the months of September to December 2021, which improved the conditions thermal, finally the technical proposal of a rural thermal house built with cement blocks added with Stipa ichu fibers can be used as a material for construction in rural houses thus attenuating low temperatures, the results obtained indicate that the house built with blocks of fiber cement significantly improves thermal characteristics compared to houses built with other conventional materials.